Analisis Pengaruh Kualitas Produk, Harga dan Strategi Promosi terhadap Kepuasan Konsumen Cafe Sap Kediri - Sutapa, Heru; Ayu Yaya H.R, Rambu Dyah (YUME : Journal of Management, 2022)
Abstract : This study aims to determine the effect of product quality (X1), price (X2) and promotion strategies (X3) on consumer satisfaction (Y) Caffe SAP Kediri. The type of research used is quantitative research which is processed by statistical methods. Data collection techniques used are primary data and secondary data. Sample selection using purposive sampling method. Research data obtained through questionnaires, interviews, and literature study. The results of the study obtained that the product quality variable had a partial significant effect on consumer satisfaction, with the results of the sig. 0.000 < 0.05. The results of the t-test of the price variable have a partially significant effect on consumer satisfaction with the results with a value of sig. 0.000 < 0.05, Test results promotion strategy variable partially significant effect on consumer satisfaction with the value of sig. 0.000 < 0.05. The results of the F test obtained a significance value of 0.000 <0.05. From the results of the analysis it can be concluded that product quality, price and promotion strategy simultaneously have a significant effect on Consumer Satisfaction Caffe SAP KeKeywords: Product Quality, Price, Promotion Strategy, Consumer Satisfaction